POLA INTERAKSI BERBASIS AGAMA PADA MASYARAKAT RAWAN KONFLIK DI KABUPATEN SIGI - A. Markarma (ISTIQRA, 2014)
As a new regency, Sigi should improve itself to organize the society life. The religion awareness in conflict-prone areas is very urgent to be improved. In the perspective of civil society, social conflicts that occur as a result of lack of public communication. Based on this assumption, researcher entitled this research: Interaction Patterns based on Religion in Conflict-Prone Communities in Sigi. Researcher focused on two sub subject: (1) how the interaction patterns based on religion in conflict-prone communities in Sigi. (2) how the implications for efforts to resolve social conflicts in Sigi regency. Research results showed that patterns of community interaction in conflict-prone areas in Sigi was pretty good. There are approximately 60% of respondents who support this conclusion. But the fabric of social interaction society merely casual relationships, not based on a good understanding of religion. Therefore, efforts to resolve social conflict is not significant. Approximately 46% of respondents believe that the faith-based social interaction patterns are less effective in the resolution of social conflicts. As a result, social interaction in conflict-prone areas in Sigi is not in line with the spirit of religion